Op amps for everyone - Carter, Bruce, 1954-; Mancini, Ron (Newnes, 2018)
Op Amps for Everyone, Fifth Edition, will help you design circuits that are reliable, have low power consumption, and can be implemented in as small a size as possible at the lowest possible cost. It bridges the gap between the theoretical and practical by giving pragmatic solutions using components that are available in the real world from distributors. The book does not just give a design with a transfer function; instead, it provides design tools based on transfer function, getting you to a working circuit so you can make the right decision on which op amp is best for the job at hand. With this book you will learn: single op amp designs that get the most out of every amplifier; which specifications are of most importance to your design, enabling you to narrow down the list of amplifiers to those few that are most suitable; strategies for making simple tweaks to the design-changes that are often apparent once a prototype has been constructed; how to design for hostile environments-extreme temperatures, high levels of shock, vibration, and radiation-by knowing which circuit parameters are likely to degrade and how to counteract that degradation.